Psychological and autonomous nervous system features of functional gastric dyspepsia and irritable bowel syndrome, duloxetine treatment efficacy - A. P. Pogromov; G. M. Dyukova; M. L. Leonova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To specify the association of symptoms, related to gastro-intestinal tract (GIT) and extraintestinal manifestations in patients with functional gastro-intestinal diseases (FGID) – functional dyspepsia (FD) and irritable bowel syndrome (IBS) – in comparison to group of patients with organic gastro-intestinal diseases (OGID), strictly following diagnostic guidelines of Rome criteria-III. To study treatment efficacy of FD and IBS patients by selective serotonin and norepinephrine re-uptake inhibitor duloxetine.Material and methods. At physical examination analysis of complaints, past history, examination data was applied. Bristol stool scale (Rome-III 2006), laboratory and instrumental methods: upper endoscopy, colonoscopy, morphological study, Helicobacter pylori breath test, routine blood biochemical tests were used. Analysis of the «associated» or extraintestinal symptoms was carried out by Screening for Somatoform Symptoms questionnaire – SOMS-2 (Rief, 1996). Psychometric testing was performed: for depression level (Beck Depression Inventory), degree of alexithymia (TAS), anxiety level (Spielberger's State/Trait Anxiety Inventory). Analysis of childhood and actual psychogenias and psychophysiological reactions in the childhood. The scale of autonomous nervous disorders was applied for assessment of autonomous status (Vein et al., 1998), for evaluation of pain phenomena of various location – visual-analog scale.Results. At comparative analysis of gastroenterological symptoms in FGID and OGID patients in general it was revealed, that for majority of them no essential difference between organic and functional groups exits. Significant differences in predominance of esophageal complaints were revealed in FGID patients. Scores of associated symptoms and autonomous changes were significantly higher in FGID patients, as well as predominance of childhood psychogenias. Results of psychometric tests demonstrated, that in FGID patients the levels of depression and trait anxiety was significantly higher. According to aims of investigation all FGID patient received duloxetine treatment. After cessation of therapy all patients were monitored for one year with no relation to duration of treatment. After 8 wks of treatment clinical improvement was accomplished in the majority of patients, however preserved symptoms and signs have required continuation of therapy up to achievement of clinical remission. Duration of treatment was 4 to 9 months.Conclusions. At functional gastro-intestinal diseases psychopathologic and behavioural symptoms prevail in clinical pattern. No significant differences in gastrointestinal symptoms in patients with functional and organic gastro-intestinal diseases was found. Treatment of patients with the functional diseases by double-acting antidepressant duloxetine not only reduces psychological and autonomous nervous system disorders substantially, but also relieves main gastro-intestinal symptoms. Further studies for estimation of optimal dose and duration of treatment are requires.